2021
DOI: 10.3390/jcm10153282
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Alanine Aminotransferase Values with Extubation Failure in Adult Critically Ill Patients: A Retrospective Cohort Study

Abstract: Background: Liberation from mechanical ventilation is a cardinal landmark during hospitalization of ventilated patients. Decreased muscle mass and sarcopenia are associated with a high risk of extubation failure. A low level of alanine aminotransferase (ALT) is a known biomarker of sarcopenia. This study aimed to determine whether low levels of ALT are associated with increased risk of extubation failure among critically ill patients. Methods: This was a retrospective single-center cohort study of mechanically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Generally, high ALT or AST values (>40 IU/L) are considered pathological and reflect liver damage, caused by hepatitis, etc. (11). Another study also reported that low ALT activity in the peripheral blood is a surrogate marker for low general body muscle mass and sarcopenia (12).…”
Section: Introductionmentioning
confidence: 97%
“…Generally, high ALT or AST values (>40 IU/L) are considered pathological and reflect liver damage, caused by hepatitis, etc. (11). Another study also reported that low ALT activity in the peripheral blood is a surrogate marker for low general body muscle mass and sarcopenia (12).…”
Section: Introductionmentioning
confidence: 97%
“… 15 Premature discontinuation of ventilation can place the respiratory and cardiovascular systems under severe stress, hindering the patient’s recovery. However, prolonged use of ventilation can lead to a series of complications such as disuse atrophy of the diaphragm and ventilator-associated pneumonia, 16 , 17 while also prolonging the patient’s hospital stay and increasing the economic burden on the family. Therefore, identifying indicators that can efficiently and accurately predict the outcome of weaning is of great clinical significance to improving the success rate of weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Signi cantly decreased serum ALT is an independent risk factor for mortality in the elderly population [21]. Again, a study including 329 patients with a median age of 62.4 years reported that sarcopenia and low ALT values, an established biomarker of frailty, are an independent risk factor for extubation failure in hospitalized patients [22]. A study examining the data of 51 831 patients with a mean age of 70.88 showed that low ALT < 10 IU/l values were associated with mortality [23].…”
Section: Discussionmentioning
confidence: 99%